EVALUASI RASIONALITAS PENGGUNAAN OBAT GASTRITIS DI BEBERAPA RUMAH SAKIT : NARRATIVE LITERATURE RIVIEW - Hernandi, Baso; Sukandar, Elin Yulinah (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Gastritis is inflammation of the gastric mucosa caused by various factors, including lifestyle, food, irritation and infection. Inflammation of the stomach lining causes stomach ulcers. Based on the World Health Organization (WHO), 40.8% of Indonesia's population suffers from ulcers, and this disease is common in several large areas such as Jakarta, which is 274,396 cases out of 238,452,952 people. The World Health Organization (WHO) has turned its attention to the irrational use of drugs because more than 50% of drugs are prescribed, shipped, and sold globally without patient compliance or proper use. The purpose of this study was to review the rationality of the use of gastritis drugs in several hospitals. This study is a review of accredited journals and articles from the publication years 2019-2024. The data collection method involved analyzing fifteen journals using the relevant keywords